The Approach to Personnel Management in Using Good Information Technology Systems and Using Online Social Media Creatively - Ongprachayakul, Pannisa (Science, Technology, and Social Sciences Procedia, 2021)
At present, both public and private organizations use information technology and social media systems within the organization and are an important part of the organization’s operation. There is a risk of problems from both the system and the personnel who use it. The risk of problems can cause damage to the organization in its operations, therefore personnel management guidelines for using a good information technology system and using social media have 3 components: Information technology systems, personnel and social media. The organization applies the principles adopted by international standards and laws on electronic transactions to formulate policies and plan to manage systems and use of online media accordingly and manage personnel to know how to use the system and online media effectively for both the organization and the organization itself.